PENGARUH BUDAYA ORGANISASI, MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN PERTANAHAN KABUPATEN GIANYAR - I Made Dwi Narayana; Anak Agung Dwi Widyani; Tiara Carina (VALUES, 2024)
Companies and government agencies want optimal employee performance in the interests of increasing work results and company and agency profits. There are many factors that influence employee performance, including organizational culture, work motivation and job satisfaction. Likewise, at the Gianyar Regency Land Agency Office, organizational culture, work motivation and job satisfaction are factors that can influence employee performance. There is attention and findings regarding issues of organizational culture, work motivation and job satisfaction in an effort to improve and improve employee performance in accordance with the aim of this research to determine the influence of organizational culture, work motivation and job satisfaction on employee performance at the Gianyar Regency Land Agency Office. The population in this study was 158 people. The number of samples in this study was 105 people. The sampling technique used was proportional random sampling. Data analysis in this study used Multiple Linear Regression Analysis using the IBM SPSS Statistics 25 application. The research results show that organizational culture has a positive and significant effect on employee performance at the Gianyar Regency Land Agency Office. Work motivation has a positive and significant effect on employee performance at the Gianyar Regency Land Agency Office. Job satisfaction has a positive and significant effect on employee performance at the Gianyar Regency Land Agency Office.